Safe and Sustainable Traditional Production: The Water Buffalo in Asia - Deb, Gautam K.; Nahar, Talukder N.; Duran, Peregrino G.; Presicce, Giorgio A. (Frontiers in Environmental Science, 2016)
The water buffalo (Bubalus bubalis) is considered an efficient converter of poor quality forages into high quality milk and meat. This species is ubiquitous, with prevalence though in Asian and Mediterranean countries. From a genetic standpoint, the species is characterized by two main subspecies: river and swamp type. The former to be found predominantly in Mediterranean countries, whereas the latter is found only in the Asia continent. At present, the majority of the total world buffalo population is distributed in Asia, holding around 95% of the available stock. There, animals are mostly fed on low quality roughages and crop residues with poor nutritive value, resulting inevitably in reduced productive and reproductive performances. A distinctive differential production system is in effect between river and swamp type buffaloes, due to a significant production capacity of the two sub-species. An overview of production systems and their sustainability in the two sub-species with an emphasis on country of origin and feed availability is presented.